Pathophysiology and Clinical Utility of Non-coding RNAs in Epilepsy - Shao, Yiye; Chen, Yinghui (Frontiers in Molecular Neuroscience, 2017)
Epilepsy is a common neurologic disorder. The underlying pathological processes include synaptic strength, inflammation, ion channels and apoptosis. Acting as epigenetic factors, non-coding RNAs (ncRNAs) participate in the regulation of pathophysiologic processes of epilepsy and are dysregulated during epileptogenesis. Aberrant expression of ncRNAs are observed in epilepsy patients and animal models of epilepsy. Furthermore, ncRNAs might also be used as biomarkers for diagnosis and the prognosis of treatment response in epilepsy. In this review, we will summarize the role of ncRNAs in the pathophysiology of epilepsy and the putative utilization of ncRNAs as diagnostic biomarkers and therapeutic targets.